2013
DOI: 10.5942/jawwa.2013.105.0066
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for assessing optimized corrosion control treatment of lead and copper

Abstract: Three strategies are commonly used to optimize corrosion control: adjusting pH and alkalinity, developing Pb(iv) scale by maintaining free chlorine residuals throughout the distribution system, and applying orthophosphate‐based corrosion inhibitors at appropriate dosages and pH ranges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…It is well documented that the use of phosphate inhibitors, especially orthophosphate, can significantly reduce lead levels by forming a scale to reduce the amount of soluble lead that is leached into the water (Brown et al , Cardew ). PWD's target phosphate dosage goal for orthophosphate has steadily increased since uniform CCT was first implemented at all three WTPs.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that the use of phosphate inhibitors, especially orthophosphate, can significantly reduce lead levels by forming a scale to reduce the amount of soluble lead that is leached into the water (Brown et al , Cardew ). PWD's target phosphate dosage goal for orthophosphate has steadily increased since uniform CCT was first implemented at all three WTPs.…”
Section: Resultsmentioning
confidence: 99%
“…Utilities generally responded quickly and effectively to meet the new requirements of the LCR after the regulation's promulgation. Figure shows the 90th percentile lead distribution before and after the LCR for 166 utilities serving over 50,000 persons (Brown et al ). These utilities had 90th percentile lead data above the 15 μg/L action level (AL) before initiating measures to comply with the LCR—so these were the utilities serving more than 50,000 people with the highest lead levels at that time.…”
Section: A Daunting Taskmentioning
confidence: 99%
“…Therefore, corrosion control in the United States for Lead and Copper Rule (LCR) compliance has focused on treatment to reduce the distributed water's plumbosolvency, or capacity to dissolve lead from lead‐containing materials in the service lines or premise plumbing (Brown et al , EES , Schock ). Brown et al () identified three treatment strategies that generally encompass the corrosion control treatment (CCT) used by utilities for LCR compliance: Control of pH and alkalinity Development and maintenance of insoluble Pb(IV) scale under oxidized conditions Use of orthophosphate‐based corrosion inhibitors …”
mentioning
confidence: 99%